Environmentally friendly thermoacoustics refrigeration: theory and applications - Mohd. Ghazali, Normah (2015)
Concerns over the danger imposed on our environment from hazardous refrigerants released from the industry have prompted extensive and intensive research into alternatives coolants and technology, to replace or reduce our dependence on the current systems. For thermoacoustics technology, numerous reports have established the refrigeration applications of thermoacoustic cooling without compressors and refrigerants. Significant cooling effects obtainable in a thermoacoustic resonator fitted with a heat exchanging stack and operated at resonance has continued to attract researchers to this potentially challenging area.Thermoacoustic refrigeration is supposedly simple with few or no moving parts and consequently cheaper to maintain, and definitely an environmentally friendly technology. Almost thirty years have passed since the first thermoacoustic crycooler was deemed succesful and the technology in thermoacoustic cooling is still considered young with only a handful of researchers seriously and actively involved since then. This paper discussed the basic theory behind thermoacoustic cooling, the developments since the first cooling system was completed and associated issues that need to be addressed in the experimental and modeling areas related to the thermoacoustic phenomena.